Heterogeneity in α‐synuclein subtypes and their expression in cortical brain tissue lysates from Lewy body diseases and Alzheimer's disease. (3rd December 2018) - Vaikath, N. N.; Erskine, D.; Morris, C. M.; Majbour, N. K.; Vekrellis, K.; Li, J.‐Y.; El‐Agnaf, O. M. A.
Abstract : Aims: Lewy body diseases are neuropathologically characterized by the abnormal accumulation of α‐synuclein (α‐syn) protein within vulnerable neurons. Although studies have evaluated α‐syn in post mortem brain tissue, previous findings have been limited by typically employing pan‐α‐syn antibodies that may not recognize disease‐relevant forms of protein. We investigated the presence of α‐syn species present in post mortem brain tissues from Lewy body disease and Alzheimer's disease. Methods: Soluble and insoluble/aggregated α‐syn from frontal cortex of post mortem brain tissues form Parkinson's disease (PD), dementia with Lewy bodies (DLB), Alzheimer's disease (AD) and aged control cases were sequentially extracted using buffers with increasing detergent concentrations. Enzyme‐linked immunosorbent assay (ELISA) was used to quantify the levels of total‐, oligomeric‐ and phosphorylated‐Ser129‐α‐syn (t‐, o‐ and pS129‐α‐syn). ELISA data were validated by western blot and compared to histological data from the same region of the contralateral hemisphere. Results: There was no difference in t‐α‐syn levels between groups in the aqueous‐soluble, detergent‐soluble or urea‐soluble tissue fractions. However, aqueous‐soluble non‐phosphorylated o‐α‐syn was increased not only in PD and DLB but also in AD without neocortical Lewy bodies. In PD and AD, pS129‐α‐syn was increased in the detergent‐soluble tissue fragment and, in AD, this was positively correlated with the burden of tau pathology. Increased levels of urea‐soluble pS129‐α‐syn were demonstrated only in DLB tissue lysates but this did not correlate with Lewy body pathological burden. Conclusions: Taken together, these findings suggest that DLB have elevated levels of insoluble pS129‐α‐syn, but that increased levels of aqueous‐soluble o‐α‐syn and detergent‐soluble pS129‐α‐syn are also observed in PD and AD, suggesting different changes to α‐syn across the spectrum of neurodegenerative proteopathies.